2016
DOI: 10.2807/1560-7917.es.2016.21.43.30382
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of syphilis in men who have sex with men and risk management strategies, Germany, 2015

Abstract: In Germany, the number of reported syphilis cases increased between 11% and 22% per year between 2010 and 2014. We analysed syphilis surveillance data and data of four behavioural surveys on men who have sex with men (MSM) in Germany (2003, 2007, 2010, 2013) to assess if this rise is ongoing and to find possible explanations for it. Syphilis notifications increased in 2015 by 19% to a total of 6,834. This was mainly due to increasing notifications in MSM of all age groups in larger German cities. Data from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 23 publications
0
36
1
7
Order By: Relevance
“…Increased prevalence of syphilis among MSM has been reported globally (6)(7)(8)(9)(10). This is assumed to be due to increased high-risk sexual behaviors, including unprotected sex, because successful reduction in HIV transmission has been reported in association with preexposure prophylaxis (PrEP) (10,38). A prescription of antiretroviral drugs for PrEP is not officially supported in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased prevalence of syphilis among MSM has been reported globally (6)(7)(8)(9)(10). This is assumed to be due to increased high-risk sexual behaviors, including unprotected sex, because successful reduction in HIV transmission has been reported in association with preexposure prophylaxis (PrEP) (10,38). A prescription of antiretroviral drugs for PrEP is not officially supported in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…. The majority of syphilis patients are males, with the majority of cases being attributable to men who have sex with men (MSM) (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Of particular importance are local genital tract inflammatory processes that increase HIV shedding in semen rendering an individual more infectious than is apparent from his blood plasma viral load (Kalichman, Diberto, & Eaton, 2008;Pilcher et al, 2006). Thus, increases in condomless anal sex and exposure to STI will ultimately diminish the prevention benefits of HIV treatments (Jansen, Schmidt, Drewes, Bremer, & Marcus, 2016;Katz, Dombrowski, Bell, Kerani, & Golden, 2016;Payne, Lawrence, Soni, Llewellyn, & Dean, 2016;Sood, Wagner, Jaycocks, Drabo, & Vardavas, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown an increase in the rate of unprotected sex [15] and consequently in the spread of sexually transmitted diseases (STDs) [8]. Rising syphilis rates were observed in the city in which we conducted our study (Cologne, Germany: 2014, n = 313; 2015, n = 332; 2016, n = 347; 2017, n = 418) [16].…”
Section: Discussionmentioning
confidence: 99%